Randomness test of cryptographic one-to-many reversible mapping for ipv6 address generation - Hakiem, Nashrul; Siddiqi, Mohammad Umar; Jarot, Sigit Puspito W.; Priantoro, Akhmad Unggul (Little Lion Scientific Islamabad Pakistan, 2014)

(untitled)
This paper presents simulation results on randomness test of a cryptographic one-to-many reversible mapping between user space and the IPv6 address space. A one-to-many reversible mapping mechanism is developed which may be embedded into a DHCPv6 (Dynamic Host Configuration Protocol for IPv6) server in the stateful mode within an enterprise local area network (LAN). Each time a user accesses the network, the DHCPv6 server is able to assign a dynamic IPv6 address. The dynamic address (obtained through one-to-many mapping) is to protect the user from unwanted behavior analysis exploiting IPv6 addresses, thus protecting user privacy. However, the dynamic address can be uniquely linked to the user (through many-to-one reversible mapping) if the need arises. The randomness of the dynamic address (one-to-many mapping) for IPv6 address assignment is evaluated based on uniformity using monobit (frequency) test, and avalanche effect is evaluated using Hamming distance tests. Simulation results show that the randomness in terms of uniformity (occurrence of 1's or 0's are around 50%) and the Hamming distance (the difference between Interface IDs at approximately 50%) are accepted. The decision rule of randomness is set at the 1% significance level with the Pvalue of monobit (frequency) test, and the Pvalue in Hamming distance tests is taken to be more than 0.01. IPv6 addresses generated by a one-to-many reversible mapping mechanism are considered to be random with a confidence level of 99%.